The words of the Holy Qurʾān and Their Renewed Meanings: Kata-kata dalam Al-Qur'ān dan Makna yang Diperbaharui - Al-Balushi, Rashid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: This study emerges from the need to understand semantic shifts in the Qurʾān more comprehensively, particularly for the terms “qāʾil” and “al-Amānah,”. The main objective is to show that the words of the Holy Qurʾān may acquire new meanings or usages, based on various factors, and that the expanded meanings of Qurʾānic words have implications for the overall understanding of the respective verses. The methodology involves reference to classical and modern lexicons, as well as contextual inquiries grounded in tafsīr literature. The data were analyzed qualitatively by integrating different perspectives. The main results: “qāʾil,” commonly understood as “one who speaks,” may also refer to “one at midday,” while “al-Amānah” does not necessarily refer to “material trusts or religious rites,